Population Based Survey of Glucose-6-Phosphate Dehydrogenase (G6PD) Deficiency among People Living in Terai Districts of Nepal (Tribhuvan University Journal of Microbiology, 2018)
Objective: This study was carried out to determine the prevalence of Glucose-6-phosphate dehydrogenase (G6PD) deficiency among population of selected malaria endemic districts in central and eastern terai of Nepal.Methods: Six hundred seventy whole blood samples were collected from the indigenous peoples community, identified based on district public health office records for G6PDd in the past from Jhapa, Morang and Dhanusha districts endemic to malaria, during April to June 2013. Collected blood samples were tested on the sites by using BinaxNow G6PD test kit and CareStartTM G6PD test kits.Results: The G6PD deficiency was found to be in 6.1% and 6.3% in BinaxNow and CareStartTM respectively. In 42 G6PD deficient cases number of male to female ratio was almost equal. Higher proportions of deficient cases were from Rajbanshi and Santhal communities than others. Highest number of deficient cases was in Jhapa followed by Morang and Dhanusha districts respectively.Conclusion: G6PD deficiency in indigenous population group in eastern and central terai are heterogenous. So the testing of G6PD before initiation of radical treatment of Plasmodium vivax infection would be important for reducing the risk of hemolysis following Primaquine (PQ) administration. Rational evidence-based PQ administration may be helpful in contributing towards the elimination of malaria from the country.